2018
DOI: 10.1038/s41586-018-0206-z
|View full text |Cite
|
Sign up to set email alerts
|

Induction and transcriptional regulation of the co-inhibitory gene module in T cells

Abstract: Expression of co-inhibitory receptors, such as CTLA-4 and PD-1, on effector T cells is a key mechanism for ensuring immune homeostasis. Dysregulated co-inhibitory receptor expression on CD4+ T cells promotes autoimmunity while sustained overexpression on CD8+ T cells promotes T cell dysfunction or exhaustion, leading to impaired ability to clear chronic viral infections and cancer1,2. Here, we used RNA and protein expression profiling at single-cell resolution to identify a module of co-inhibitory receptors th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

21
365
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 371 publications
(388 citation statements)
references
References 41 publications
21
365
2
Order By: Relevance
“…This expression pattern is consistent with a "cassette" of coordinately regulated coinhibitory receptors recently described in the literature. 29 Of note, CITRUS also identified a separate cluster that expressed high 2B4 but low PD-1, TIM-3, and (Figure 3C,D). There was also no significant difference between the abundance of cells expressing 2B4 (25 457) at this time point ( Figure 3D).…”
Section: Anti-cd28 Dab Does Not Differentially Affect the Expressiomentioning
confidence: 87%
See 1 more Smart Citation
“…This expression pattern is consistent with a "cassette" of coordinately regulated coinhibitory receptors recently described in the literature. 29 Of note, CITRUS also identified a separate cluster that expressed high 2B4 but low PD-1, TIM-3, and (Figure 3C,D). There was also no significant difference between the abundance of cells expressing 2B4 (25 457) at this time point ( Figure 3D).…”
Section: Anti-cd28 Dab Does Not Differentially Affect the Expressiomentioning
confidence: 87%
“…At 14 dpi, there was a significant decrease in the abundance of cells found within parent cluster 17 654 in both the CTLA-4Ig-and anti-CD28-dAb treated samples as compared to no treatment ( Figure 3A,B), but the abundance of cells in cluster 17 654 was not different between the two treatment groups. 29 Of note, CITRUS also identified a separate cluster that expressed high 2B4 but low PD-1, TIM-3, and exhaustion cassette of PD-1 + , TIM-3 + , and TIGIT + was still present (25 466), there was no difference in the abundance of cells within this node between experimental groups ( Figure 3C,D). This expression pattern is consistent with a "cassette" of coordinately regulated coinhibitory receptors recently described in the literature.…”
Section: Anti-cd28 Dab Does Not Differentially Affect the Expressiomentioning
confidence: 92%
“…In a recent article, the authors and colleagues identified a new gene module that is induced by the regulatory cytokine, interleukin‐27 (IL‐27), and is found in multiple non‐responsive T‐cell states, such as exhaustion, dysfunction and tolerance . This study uncovered novel immune checkpoint molecules poised to become therapeutic targets.…”
mentioning
confidence: 99%
“…Although many co‐inhibitory molecules that modulate T‐cell phenotype in autoimmune diseases have been investigated, it was unclear whether there is a common anchor underlying the expression of these molecules. Here, using single‐cell RNA‐seq and single‐cell mass cytometry, the author and colleagues showed the co‐expression of these co‐inhibitory molecules in the highly immunosuppressive tumor microenvironment . The core of the expression consisted of known co‐inhibitory molecules, such as PD‐1, TIM‐3, LAG‐3 and TIGIT, and co‐expressed with multiple new cell‐surface receptors.…”
mentioning
confidence: 99%
See 1 more Smart Citation